Nasal Spray Formulations Based on Combined Hyalurosomes and Glycerosomes Loading Zingiber officinalis Extract as Green and Natural Strategy for the Treatment of Rhinitis and Rhinosinusitis - Eleonora Casula; Maria Letizia Manca; Matteo Perra; Jose Luis Pedraz; Tania Belen Lopez-Mendez; Antonio Lozano; Esteban Calvo; Marco Zaru; Maria Manconi (MDPI AG, 2021)
A total green nanotechnological nasal spray has been manufactured and proposed as an alternative treatment of rhinitis and rhinosinusitis. It was obtained by combining the strengthening effect of liposomes on barrier function, the hydrating and lubricating properties of sodium hyaluronan and the anti-inflammatory and antioxidant activities of the extract of Zingiber officinalis. To this purpose, the extract was loaded in special phospholipid vesicles immobilized with hyaluronic acid (hyalurosomes), which were further enriched with glycerol in the water phase. Liposomes and glycerosomes were prepared as well and used as reference. Vesicles were oligolamellar and multicompartment, as confirmed by cryogenic transmission electron microscopy (cryo-TEM) observation, small in size (~140 nm) and negatively charged (~−23 mV). Spray characteristics were evaluated by using the Spraytec® and instant images, from which the plume angle was measured. The range of the droplet size distribution and the narrow spray angle obtained suggest a good nebulization and a possible local deposition in the nasal cavity. In vitro studies performed by using human keratinocytes confirmed the high biocompatibility of vesicles and their ability to effectively counteract oxidative damage on cells induced by hydrogen peroxide. The overall collected data suggest that our vesicles are suitable as nasal spray.